RELATIONSHIP BETWEEN MEDIA EXPOSURE AND THE AGE OF MENARCHE - Fahmi Fuadah (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2020)
Menarche is the first menstruation marked by the discharge of blood from the vagina due to decay of the endometrial wall, factors affecting the age of menarche include nutritional status, socioeconomic, physical abnormalities, audiovisual, social and genetic environment. One of the factors that influence the occurrence of early menarche is caused by strong stimuli from the external factor, one of which is through exposure to information media, both print and electronic. Information media exposure and the speed of adolescent puberty which indirectly causes the acceleration of the age of menarche. Today, teenagers tend to be influenced by information media easily, misinformation about reproduction, and adult websites. The purpose of this study was to determine the relationship between media exposure and the age of menarche. This study used a cross-sectional approach. The total sample was 173 women adolescents chosen using a simple random sampling technique. Data were collected using interviews and a survey and then analyzed using the Chi-Square test. The results showed that the most age of menarche was 11 years (43.3%), there was a relationship between media exposure with menarche age (p <0.05). It is recommended for each student to be able to choose the right information about reproductive health, it would increase their knowledge and insight about reproductive health.Keywords: Adolescent, Media, Menarche Age.